Coastal informatics web atlas design and implementation - Wright, Dawn J. 1961-; Dwyer, Ned; Cummins, Valerie 1974-; Gale Group (Hershey, Pennsylvania Information Science Reference, 2011)
Reviews and presents the latest developments in the emerging field of coastal web atlases through a series of case studies giving practical guidance on geographic data management and documentation through standards-based metadata, as well as making underlying geographic databases interoperable.
section 1. Principles -- section 2. Coastal web atlas case studies around the world -- section 3. Coastal web atlas management and governance issues.
Description based on print version record.
"Premier reference source."--Cover.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Coasts -- Geographic information systems; Coastal mapping; Management information systems; Electronic books